Scores Consumption of Functional Foods based on Local Foods in Pregnant Women Buginese in the city of Makassar (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background Recent evidence is known that functional foods are foods that provide the latest prospectsfor preventing nutritional problems not only because of their macro and micro nutrient content but theirbioactive components that have an effect on the methylation process at the cellular level.Objective: the purpose of this study was to determine the consumption of functional foods based on localfoods in pregnant women in Makassar CityMethod: A cross sectional study design. The sample size was 647 pregnant women taken from 41 Puskesmasin Makassar City, except the Sangarrang Kepulauan Puskesmas. Functional food intake was collectedusing the FFQ method, Macro and micro nutrient intake with Food recall 2 x 24 hours. The data collectionenumerators were 21 graduates from Nutrition III / IV graduates. Enumerators are trained for two days.Results; showed that functional foods consumed by pregnant women based on local foods are sources offiber, probiotics, Vitamin C, carotenoids, omega 3/9 and folifenol respectively (39.03 ± 36.78), (21.15 ±7.74), (38.44 ± 30.9), (90.04 ± 50.53), (83.42 ± 60.42) and 166.57 ± 92.66). Conclusion; is that consumptionof functional foods based on local foods in pregnant women is good.